1972
DOI: 10.1002/macp.1972.021540103
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical polymerization of monomers with conjugated triple bonds

Abstract: cular Preprint. Vol. 11, p. 908). 35 G. WEGNERwerden, da13 die polymeren Diacetylene entweder durch die Butatrien-Struktur oder eine mesomere en-in-Struktur beschrieben werden konnen. Die Polymerisation der farblosen Monomerkristalle wird durch Bestrahlung mit UV-oder energiereicher Strahlung oder aber durch Tempern der Monomerkristalle unterhalb ihres Schmelzpunktes bewirkt. Tief rot, blau oder schwarz gefarbte Polymerkristalle werden dabei erhalten, die einen starken Dichroismus aufweisen. Die Faserachse ist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
198
0
6

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 520 publications
(213 citation statements)
references
References 15 publications
9
198
0
6
Order By: Relevance
“…Examples of the former polymerization have included oxacyclobutanes such as 1,3,5-trioxane, 2,3 diolefins undergoing four-center type photopolymerization 4,5 and monomers with conjugated triple bonds such as substituted diacetylenes. 6,7 On the other hand, the first polymer whisker was obtained by the cationic ring-opening polymerization of 1,3,5-trioxane. [8][9][10] The obtained polyoxymethylene whiskers were 1-2 mm in width and 10-50 mm in length.…”
mentioning
confidence: 99%
“…Examples of the former polymerization have included oxacyclobutanes such as 1,3,5-trioxane, 2,3 diolefins undergoing four-center type photopolymerization 4,5 and monomers with conjugated triple bonds such as substituted diacetylenes. 6,7 On the other hand, the first polymer whisker was obtained by the cationic ring-opening polymerization of 1,3,5-trioxane. [8][9][10] The obtained polyoxymethylene whiskers were 1-2 mm in width and 10-50 mm in length.…”
mentioning
confidence: 99%
“…* Discussion. Wegner (1969Wegner ( , 1972 has shown that large and almost defect-free monocrystalline polymers can be obtained via solid-state polymerization of diacetylenes…”
mentioning
confidence: 99%
“…1 (Wegner, 1969(Wegner, , 1972(Wegner, , 1977. Polymerization may be initiated by thermal, photochemical or mechanical techniques.…”
Section: Introduction Many Diacetylenes (General Formulamentioning
confidence: 99%